PENGARUH PROFITABILITAS, PAJAK PENGHASILAN DAN UKURAN PERUSAHAAN TERHADAP KEPUTUSAN TRANSFER PRICING - Munawaroh, Munawaroh; Nadia Zalviana (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2021)
This research examined the effects of profitability, income tax, and company size on transfer pricing decisions in agricultural and mining sector companies listed on Indonesia Stock Exchange (IDX) in the period of 2016 to 2018. The sampling technique chosen was by purposive sampling method, thus, 42 samples were selected. Hypothesis testing used logistic regression analysis. As a result, this study found that only by partially company size has a significant effect on transfer pricing decisions